Efektivitas Pendekatan Saintifik dalam Meningkatkan Hasil Belajar IPA Siswa SD - Nurul Qolbi; Adrias Adrias; Aissy Putri Zulkarnaen (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to examine the effectiveness of the scientific approach in improving Natural Sciences (IPA) learning outcomes among Elementary School students. The method used is a literature review with a descriptive qualitative approach by analyzing various scientific sources such as journal articles, books, and relevant research reports from the past five years. The findings indicate that the scientific approach has a positive impact on students' understanding of science concepts, critical thinking skills, as well as motivation and engagement in the learning process. This approach encourages students to actively participate in scientific processes through the stages of observing, questioning, experimenting, reasoning, and communicating. These stages help make learning more meaningful, contextual, and aligned with students’ cognitive development. However, its implementation still faces several challenges, such as limited facilities and infrastructure, constrained instructional time, and the lack of teacher training in applying this approach effectively. Therefore, support from various stakeholders—including schools, government, and the community—is needed to overcome these obstacles and enhance the quality of science education. Overall, the scientific approach is considered effective in creating interactive, reflective, and student-centered science learning at the Elementary School level.